The forgotten - Applegate, Katherine; Copyright Paperback Collection (Library of Congress) (New York : Scholastic, 1997)
The Animorphs, Jake and Ax steal a Yeerk Bug fighter and end up in another time and another place, with no way home.
"An Apple paperback" -- T.p.
"An Apple paperback."
Keywords: Science fiction; Metamorphosis -- Fiction; Young adult fiction